PENGARUH DEBT TO ASSET RATIO, RETURN ON ASSETS, DAN CURRENT RATIO TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SUBSEKTOR APPAREL AND LUXURY GOODS TAHUN 2021-2024 - Salsabilla Dwiyanti (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2025)
A company's financial health reflects the quality of its performance. One of the affected subsectors is Apparel and Luxury Goods, where several companies have recorded consecutive losses in recent years, leading to bankruptcy. Financial Distress can actually be detected earlier through financial ratio analysis. Therefore, this study aims to analyze the influence of the Debt to Asset Ratio (DAR), Return on Assets (ROA), and Current Ratio (CR) on Financial Distress. The study population consists of companies in the Apparel and Luxury Goods sub-sector listed on the Indonesia Stock Exchange from 2021 to 2024. The sample consists of 10 companies that meet the criteria, selected using non-probability sampling techniques with purposive sampling methods. The method used is a quantitative approach with multiple linear regression analysis techniques using SPSS 27 software. Financial Distress is measured using the Springate model. The results indicate that DAR, ROA, and CR simultaneously influence Financial Distress. Partially, ROA and CR have a significant positive effect on Financial Distress, but DAR does not have a significant effect on Financial Distress. Keywords: Debt to Asset Ratio; Return on Assets; Current Ratio; Financial Distress; Springate